The Christmas wager - Cassidy, Holly (G.P. Putnam's Sons, 2023)
"When L.A.-based real estate developer Bella Ross arrives in the sleepy mountain town of Maple Falls, she has one mission: to acquire the local failing Christmas shop, Always Noelle, securing the promotion of her dreams. Nothing can get in her way. Except the shop owner's stubborn grandson, Jesse Harrison. Both refuse to budge, until an unlikely wager is struck: Bella and Jesse will compete in the Maple Falls Holiday Games, an annual tradition of eccentric feats of strength and skills. Winner decides the selling price. They'll give each other a run for their money, but as the competition heats up, Bella and Jesse's icy feelings toward each other begin to thaw. It'll take a Christmas miracle for them to admit there's a spark, but what if it's just another game?"--